Factors influencing demand for Islamic bank products in Sri Lanka - Subaideen Issath Nimsith; Mohamed Saleem Ahamed Riyad Rooly; Fathima Ilma (Journal of Enterprise and Development (JED), 2024)
Purpose — The demand for Islamic banking products and services has been increasing globally over the past decade, including in Sri Lanka. However, the factors behind this surge are not yet fully understood. The aim of this research is to investigate the factors influencing the demand for Islamic banking products in Sri Lanka.Method — Primary data were collected through the distribution of questionnaires, which were distributed among 650 customers of Amana Bank PLC island-wide across its 33 branches. Convenience sampling techniques were employed for data collection. The Statistical Package for Social Sciences (SPSS) was utilized for analyzing the factors influencing the demand for Islamic banking products in Sri Lanka. Statistical methods, including regression analysis, correlation analysis, and a reliability test, were employed to analyze the collected data.Result — The findings indicate a robust relationship between factors such as religiosity, attitude, awareness, and reputation, and the demand for Islamic banking products in Sri Lanka. According to the regression analysis, awareness was identified as having the greatest impact on the demand for Islamic banking products, while reputation, attitude, and religiosity were determined to be the second, third, and least impactful factors, respectively.Novelty  — This research is pioneering in a country like Sri Lanka, where it is still in the developmental stage, and the majority of the population is non-Muslim. The findings offer valuable insights for policymakers in the Islamic banking and finance sectors, guiding them in formulating strategies to attract a broader customer base for their products and services among both Muslim and non-Muslim customers.